Recency Effects in the Auditor's Belief-Revision Process - Tubbs, Richard M.; Messier, William F.; Knechel, W. Robert (The Accounting Review, 1990)
[Auditing has been characterized as a sequential process of obtaining and evaluating evidence (Gibbins 1984). During this process, auditors continually update their beliefs about the audit assertion being examined. Recently, Hogarth and Einhorn (1989) have posited a belief-adjustment model for updating beliefs. Based on a sequential anchoring and adjustment strategy, the model has important implications for auditors concerning the effects of the order in which evidence is evaluated. The model predicts that the order in which evidence is received has no effect on the belief-revision process when the evidence is consistent (either all positive or all negative). However, when the evidence is mixed (positive and negative), the model predicts that a recency effect will occur. Ashton and Ashton (1988) tested an earlier version of this model with experienced auditors in "simplified, well-defined settings" and found results consistent with the model's predictions. They suggested that their findings should be tested in more realistic audit contexts. Hogarth and Einhorn (1989) have suggested that findings of recency or primacy may be influenced by task complexity. Therefore, the current study tests the predictions of the model using content-rich audit scenarios. Four experiments were conducted involving 251 experienced auditors. The first experiment tested for a lack of order effect using consistent positive evidence, and the second experiment tested for a lack of order effect using consistent negative evidence. The third and fourth experiments tested for recency effects using mixed evidence with either two or four pieces of evidence. The results of the first two experiments indicated that order of evidence was not significant. Order of evidence was significant in experiment 3 in the step-by-step response condition but not in the end-of-sequence response condition. In experiment 4, order of evidence was significant in both response conditions. Therefore, the results of this empirical work support the predictions of the model, thus reinforcing the findings of Ashton and Ashton (1988).]